Left bundle branch area pacing: Electrocardiographic features. Issue 5 (7th August 2021) - Das, Asit; Chatterjeet Das, Suman; Mandal, Aniruddha
Abstract: Background: Left bundle branch (LBB) area pacing emerged as a promising alternative to His bundle (HB) pacing in difficult cases of physiological pacing and failed cases of cardiac resynchronization. So, it is important to understand ECG features of LBB area pacing in various subsets of patients. Objective: We wanted to find out different morphological patterns and characteristic ECG features of LBB area pacing. Method: Medtronic 3830 pacing lead was used to pierce the interventricular septum 1‐2 cm distal towards the RV cavity to a previously placed electrophysiology catheter at distal HB region to reach the LBB area in the right anterior oblique (RAO) 30 degree projection. We observed paced QRS morphology in lead V1 and paced QRS duration. Results: We have analyzed ECG features of 60 patients who had undergone LBB area pacing and 60 patients with RV apical pacing. LBB area pacing resulted in narrower‐paced QRS complex than conventional RV apical pacing. In patients with baseline LBBB QRS shortening from LBB area pacing was more in comparison to patients with RBBB (34.45 ± 8.07 ms vs 19.78 ± 10.24 ms, P value .004). Paced QRS morphological pattern in lead V1 was most commonly qR pattern followed by Qr pattern. Conclusions: LBB area pacing results in narrower‐paced QRS duration than RV apical pacing. The morphological pattern is most commonly a qR or Qr pattern in lead V1. Patients with baseline RBBB showed lesser paced QRS shortening in comparison to patients with baseline LBBB. Abstract : Left bundle branch area pacing results in narrower paced QRS duration than right ventricular apical pacing with most commonly qR or Qr pattern in lead V1. Patients with baseline right bundle branch block showed lesser paced QRS shortening in comparison to patients with baseline left bundle branch block.